Clinical, histopathological and immunohistochemical study of bovine ocular squamous cell carcinoma in the Nariño department, Colombia - Cedeño Quevedo, Dario Alejandro (2020)
The clinical and histopathological aspects as well as the immunohistochemical expression of ocular squamous cell carcinoma (CCEO) were evaluated in 24 cows with ocular and periorbital neoplasms in the department of Nariño, Colombia. The variables were breed, sex, age, location, and stage of the carcinoma. Immunoexpression of p53 and CK19 was determined. There were 15 Holstein, 3 Normado, 3 Simhol, 2 Creole and one Montbéliarde cows and were classified according to age in <3 years (4%), 4-7 years (64%) and >8 years (32%). The carcinoma developed in the nictitating membrane (n=13), sclerocorneal limbus (7), lower eyelid (2), cornea (1) and in the conjunctiva (1). Ten cows presented a hypopigmented periorbital area. Small whitish gray plaques were observed on the third eyelid and cornea, irregular nodules, and cauliflower-shaped sessile warts in the limbus corneal region and eyelids. Microscopically, well-differentiated tumors showed rupture of the basal membrane, hyperchromatic nuclei, atypical mitosis, and nuclear pleomorphism. Cells arranged in cords with keratinized centers in the form of lamellar beads were found. P53, in 18 cases, showed weak immunoexpression, both in animals with normal pigmentation and with hypopigmented skin. The reactivity of CK19 was null in all the samples. The study demonstrated that morphological evaluation of ocular squamous cell carcinoma lesions using H-E staining was the best diagnostic tool, although it was not possible to classify the CCEO by stage according to the degree of microscopic differentiation.